2018
DOI: 10.1111/jgh.14378
|View full text |Cite
|
Sign up to set email alerts
|

Proposed a simple score for recommendation of scheduled ultrasonography surveillance for hepatocellular carcinoma after Direct Acting Antivirals: multicenter analysis

Abstract: The present ADRES score was simple and easy to use and may be useful for predicting risk of HCC development in short term after reaching SVR24 by DAAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 27 publications
4
42
0
Order By: Relevance
“…Furthermore, following multivariate analysis, age and AFP serum level after DAA treatment were identified as independent risk factors for HCC occurrence. These results were consistent with previous studies, which reported that elderly patients have a higher risk of developing HCC after antiviral treatment (22,23,33,34).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, following multivariate analysis, age and AFP serum level after DAA treatment were identified as independent risk factors for HCC occurrence. These results were consistent with previous studies, which reported that elderly patients have a higher risk of developing HCC after antiviral treatment (22,23,33,34).…”
Section: Discussionsupporting
confidence: 93%
“…The cumulative incidence of HCC increased significantly with higher scores (P<0.001). Previous studies have reported a stratification of HCC occurrence rate by scoring with FIB-4 and AFP after SVR or sex (31,34). However, compared with other reports, the scoring system established in the present study is simple and concise, and uses only two factors (advanced age and AFP levels after DAA treatment) to predict the risk of HCC occurrence after SVR.…”
Section: Discussionmentioning
confidence: 84%
“…It has long been known that, among patients with chronic liver disease, fluctuating or persistently elevated levels of AFP identify those at higher risk, 30,31 and AFP, alone or combined with other tumor markers, has been incorporated in models predicting HCC development in unselected cirrhotic 32 and hepatitis C virus (HCV)-infected patients. [33][34][35][36] However, because of their suboptimal accuracy and/or lack of external validation, these models are not routinely used to select patients for cost-effective surveillance.…”
Section: Alpha-fetoprotein As a Marker Of Cancer Riskmentioning
confidence: 99%
“…Unfortunately, although the biomarker has been incorporated into several multifactorial risk scores, [32][33][34][35][36] very few data are currently available on this specific topic. In a simulated model of carcinogenesis proposed for HCVinfected patients, an AFP level !20 ng/mL approximately doubled the HCC risk at 5 and 10 years in patients with either the lowest risk (women younger than 54 years, with platelet count !100,0000/mmc) or the highest risk (men older than 55 years, with platelet count <100,0000/mmc).…”
Section: Alpha-fetoprotein As a Marker Of Cancer Riskmentioning
confidence: 99%
“… 59 In addition, three Japanese studies reported that post-SVR FIB-4 (at EOT and at SVR12) and changes in FIB-4 independently predicted de-novo HCC. 50 , 55 , 60 Among investigated serological biomarkers of fibrosis was Wisteria floribunda agglutinin positive Mac-2 (WFA*M2BP), which was tested in the study by Nagata et al, reporting that WFA*M2BP assessed 24 weeks after EOT independently predicted de-novo HCC 55 ( Tables 5 and 6 ).…”
Section: Predictors Of De-novo Hccmentioning
confidence: 99%